Bernard Shaw's Ibsenisms - Ortiz, Javier (Revista Alicantina de Estudios Ingleses, 1994)
This paper deals with the complex and ambiguous admiration that Bernard Shaw professed for the Scandinavian play wright Henrik Ibsen. Throughout Shaw's professional life as a critic, he devoted a great deal of his writings to analyze and decipher Ibsen's plays for British audiences. Shaw wrote three sets of critical essays on Ibsen: The Quintessence of Ibsenism, Our Theatres in the Nineties, and The Prefaces. The article emphasizes not only the evolution in Shaw's Ibsen criticism, but also the parallelism of that evolution with the confirmation of Shaw himself as a world renown playwright. In The Quintessence Shaw discusses Ibsen's plays superficially, since he himself was in the process of becoming a playwright of the sort of Ibsen. In Our Theatres Shaw orientates his criticism around the plays themselves—he does not need to hide Ibsen's achievements from the British audience any more, as he already claims to master drama creation as much as Ibsen did in his time. Finally, in The Prefaces the critic shows many reservations towards Ibsen's dramaturgy becoming the ultimate estimations of Shaw's Ibsen interpretations.